Applying System Dynamics Approach to the Fast Fashion Supply Chain: Case Study of an SME in Indonesia - Lidia, Mariany W; Arai, Takeshi; Ishigaki, Aya; Yudoko, Gatot (School of Business and Management Institut Teknologi Bandung, 2012)
The fashion industry is the biggest contributor among the 14 creative industries in Indonesia. Nowadays many apparel companies are shifting toward the vertical integration. Since speed is everything to be successful in the apparel industry, fast fashion retailers must quickly respond to the market demand. This papers aims to develop a model of the supply chain of a small and medium scale enterprise (SME) of an apparel company in Indonesia and to propose a decision support system using System Dynamics (SD) and helps the management to identify the best business strategy. Simulated scenarios can help the management to identify the most appropriate policy to be applied in the future. Case study method was used in this research where data were collected from a typical fast fashion firm in Indonesia that produces its own wares ranging from raw materials to be ready-to-wear clothes, has three stores, a warehouse and is running online sales system. We analyses the result of many simulations in a fashion company from an operational point of view and from them we derive suggestions about the future business strategy in a small and medium fashion company in Indonesia. Keywords: system dynamics, fast fashion, supply chain management, SME, Indonesia